(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Only importation and subsidies has ensured that fossil fuel-based chemical fertilisers are available and affordable at the agricultural level in India. Biofertilizers have developed as a highly potent alternate to chemical fertilisers because to their enviromentally, easy-to-apply, pro, and expense properties. They also act as a supplement to agrochemicals by allowing plants to access micronutrients that are naturally abundant in soil or the ecosystem. Furthermore, if adequate information is made available to farmers and producers via experiences and communication, they have the possibility to be commercially sustainable in the long term. The government of India is aiming to increase the usage of bio fertilisers in combination with modern agrochemical. This paper emphasises the importance of high productivity and increased and active engagement in science and technology, public awareness programmed to increase the extra possibilities of sustainable agricultural extension, and encouraging private organisations and decision makers to consider taking a passion for science in the Indian context and for its coming years in India, as well as trying to encourage private organisations and decision makers to take an interest in this topic in the Indian context including its future in India.